Managers’ Decisions Concerning the Choice of Funding Sources in Conditions of Uncertainty on Financial Markets - Grazyna MUSIALIK (Communications of International Proceedings, 2022)
This paper aims to present the problems of optimisation of corporate financing structure. The knowledge of theoretical findings in this respect helps managers maximise the value of their enterprise and identify threats related to excessive financing with debt capital. The uncertainty on the markets resulting from the financial crisis compels managers to re-consider ways of financing their enterprises. The paper reviews the main theoretical trends in management of the capital structure in a historical order. The aspects discussed herein include the problem of estimation of the corporate debt capacity, its relation to capital structure optimisation and the problem of retaining the spare capacity to incur debt. The paper presents practitioners’ opinions regarding the relevance of factors which affect decisions taken in respect of the way of funding the businesses under their management. The final part of the paper is an attempt at identifying threats resulting from the use of debt capitals in financing the operations of companies and at formulating recommendations for the policies to be adopted in this respect in conditions of uncertainty on financial markets.
Keywords: Managers; Financial Markets; Funding Sources.